FUNCTIONS OF MECHANISMS FOR IMPLEMENTING MEDIA TOOLS IN ORGANIZING EDUCATIONAL ACTIVITIES IN HIGHER EDUCATION - K. K. Kudratov (Modern American Journals, 2025)
The introduction of media tools in education lessons is an important means of adapting to modern education, increasing student interest, and enhancing the effectiveness of the lesson. Properly selected and purposefully used media tools not only convey information, but also form conscious thinking, independent analysis, and social activity in students.
Keywords: Enlightenment Lessons, modern education, media, national pride, social activism, progressive thinking, critical thinking.